Design of digital filters by optimization techniques - Zhang, Dongye (2011)
Finite impulse response (FIR) and infinite impulse response (IIR) digital filter designs with optimization techniques are discussed in the report. An eigenvalue problem of trigonometric matrix is discussed in order to facility design of a new FIR filter with significantly reduced group delay. To design better complex coefficient FIR filters, a weighed least-squares (WLS) constraint in magnitude is imposed and combined with minimax constraints in magnitude. A new sequential optimization procedure for WLS design of IIR filters based on second-order factor (SOF) updates is proposed in the paper. By parameterization of the IIR filter’s denominator, the WLS design of an IIR filter is converted into a sequence of WLS sub-problems.